The Effect of Competitive Strategy and Quality Product on the Business Performance - Zenita Apriani; Popy Rufaidah (AIBPM Publisher, 2018)
The aim of the study is to examine the effect of competitive advantage and quality product on the business performance in the Small and Medium Enterprises (SME) in West Java’s food and beverage industries. The study is executed to 120 business owners as the respondents of the study. The data analysis used is Structural Equation Modeling (SEM) using LISREL software. Competitive strategy variables are measured using dimensions from Porter (1979), namely leadership costs, deferentiation, focus (cost focus and differentiation focus). Product quality is measured through the dimensions of Durability, Featurs, Reliability, Aestethics. The dimensions of business performance used in this study adopt the most common dimensions, namely sales growth, capital growth, market growth, and profit growth. The results of the study show that competitive strategy and quality product have a significant effect on the performance of SMEs. The results of the study resulted in the implication that business owners of SMEs have the ability to make superior decisions (such as competitive pricing, developing product variations, and focusing on serving target markets) in order to improve business performance such as increased profit and business growth. Another interesting finding is that business owners of SMEs need to prioritize the importance of producing products that have the characteristics of Durabel, attractive, reliable, and aesthetic. Keywords: West Java’s MSMEs, Competitive Strategy, Quality Product and business performance